Analisa Exchange Rate Overshooting Melalui Pendekatan Error Correction Model - Pratikto, Rulyusa (Business Administration Study Program - Universitas Katolik Parahyangan, 2012)
The main purpose of this study is to analyze the movement of Indonesian Rupiahagainst United States Dollar and its determinants. Frankel-Dornsbusch Overshootingis used as theoretical basis. It is stated that when an exchange rate is depreciatedproportionately exceeding money growth, it can be said that the exchange rate isovershoot. In other words, its value is fundamentally undervalued. By using data fromthird quarter 1997 through fourth quarter 2004 and using error correction model asits methodology, it can be concluded that in the short-run, Indonesian rupiah wasover-shooted. Furthermore, I also found that in the long-run Rupiah was convergedto its equilibrium value. These findings indicate the need of policy that can controlthe volatility of money growth, especially in the short-run horizon. Capital control isone of several policies that can be effective to maintain the stability of money growthand subsequently the exchange rate.Keywords: Frankel-Dornsbusch Overshooting, Exhange Rate, Money Supply,Error Correction Model